Determination of Use-Value, Informant Consensus Factor, and Fidelity Level of Medicinal Plants Used in Cavite, Philippines - Caunca, Evane Sullano; Balinado, Lloyd Ongpauco (Asian Journal of Biological and Life Sciences)
In developing countries like the Philippines, the use of plants as medicine plays an important role especially in providing affordable and accessible health care. However, studies to determine the use-value (UV) of these plants, the informant consensus factor (ICF), and the fidelity level (FL) have been scarce; hence, this study was conducted. This was performed in the province of Cavite, Philippines where 94 local herbalists served as informants, and were interviewed using a semistructured questionnaire about their medicinal knowledge. Here, 106 plants of medicinal value were documented and were being used for curing 16 different categories of human ailments. Several medicinal plants were found to be commonly used in the entire province based on UV. There were countless agreements among the informants in terms of the plants to be used for every disease category with ICF values ranging from 0.25 to 1.00. It revealed that most informants agreed on the use against certain infectious and parasitic diseases of Senna alata (ICF=0.43), against metabolic diseases of Mangifera indica (0.68), against digestive system diseases of Chrysophyllum cainito (0.67), against musculoskeletal diseases of Croton tiglium (0.45), against genitourinary disease of Lagerstroemia speciosa (0.67), and against other diseases symptoms not elsewhere classified of Premna odorata (0.76) after all these plants showed an FL value of 100%. This study, therefore, demonstrates the rich medicinal knowledge in Cavite, and provides a basis for future pharmacological research.
Keywords: Fidelity level; ICD-10; Informant consensus factor; Medicinal plants; Use-value